The Ideal Applicant to the Saudi Plastic Surgery Residency Program - Shah Mardan, Qutaiba N. M. (Plast Reconstr Surg Glob Open, 2021)
Securing a plastic surgery position is a demanding task for students. Although many papers have been published internationally discussing the traits and features deemed important from the point of view of plastic surgery program directors, a gap exists in the literature where this aspect is not covered in Saudi Arabia. The aim of this study was to fill this gap. METHODS: In this cross-sectional study, a survey was developed targeting all current and former Saudi plastic surgery training program directors. SPSS was used to calculate frequencies and present percentages; independent t-test was done to look for mean differences. Ethical approval was obtained from a local institution. RESULTS: All current and former Saudi plastic surgery program directors participated (n = 17), including the 8 (47.1%) current directors. When asked to rank 7 items on a scale of importance, they scored a mean of 6.2, 5.8, 5.4, 4.88, 4.82, 4.6, and 3.7 for good impression on interviews, prior experience, research experience, the grade point average (GPA), oral or poster presentations on events, the Saudi Medical Licensing Examination (SMLE), and attaining a post-graduate degree, respectively. The majority [n = 7 (41%)] considers the mode of communication, such as phone calls, as the most important aspect in recommendations. They prefer candidates who took electives/rotations at their department [n = 12 (71%)] and give more value to high-quality publications [n = 9 (47%)]. Applicant’s gender was not important. CONCLUSION: With early planning, this article could serve as a guide for medical students interested in plastic surgery to build their assets toward a successful interview.